Back to the future with old-fashioned conversations: Building relationships and individualising support with educational technologies - Heinrich E; McDonald J (Australasian Society for Computers in Learning in Tertiary Education, 2018)
Recent advances in ICT have had a profound effect on tertiary education. However, critical and social theorists caution that the relationship between teacher and student is still central and educational research over many years suggests that some of the most successful pedagogical methods are those which strengthen the relationship between teacher and student and which support student development of relatedness, competence and autonomy. In this paper, we propose a new approach to course design and organisation which builds on lessons from the past while taking advantage of the affordances of contemporary technology. We summarise data from interviews with teachers and learning support staff and conclude with our hopes for the future.
Keywords: STEM; first year teaching; personalized system of instruction; Keller plan